Influence of Melia azedarach based land use systems on economics and reclamation of salt affected soil - Nandal, D.P.S.; Kumar, Ravi (Indian Journal of Agroforestry, 2020)
A field experiment was conducted during July, 1992 to June 2002 on sandy loam saline soil to study the effect of Melia based agroforestry, forestry and agriculture land use systems on economic feasibility and reclamation of saline soil. The green matter yield of dhaincha (Sesbania aculeata), grain yield of wheat (Triticum aestivum L.) and barley (Hordeum Vulgare) and green fodder yield of berseem (Trifolium alexandrinum) remained unaffected due to Melia azedarach during the first four years of plantation. However, from fifth year onward, yield of all the crops decreased under Melia compared to control (field without trees). Dhaincha-berseem crop rotation gave the highest net present value, benefit cost ratio and internal rate of return. Plantation of Melia alone was not found economical on a saline soil. A marked decrease in electrical conductivity and increase in organic carbon and nitrogen content was recorded under all the land use systems.